Citalopram and demethylcitalopram in human milk; distribution, excretion and effects in breast fed infants - Rampono, Jonathan (Blackwell Science Inc, 2000)
AIMS: To characterize milk/plasma (M/P) ratio and infant dose, for citalopram and demethylcitalopram, in breast-feeding women taking citalopram for the treatment of depression, and to determine the plasma concentration and effects of these drugs in their infants. METHODS: Seven women (mean age 30.6 years) taking citalopram (median dose 0.36 mg kg(−1) day(−1)) and their infants (mean age 4.1 months) were studied. Citalopram and demethylcitalopram in plasma and milk were measured by high-performance liquid chromatography over a 24 h dose interval. Infant exposure was estimated (two separate methods) as the product of milk production rate and drug concentration in milk, normalized to body weight and expressed as a percentage of the weight-adjusted maternal dose. RESULTS: Mean M/P(AUC) values of 1.8 (range 1.2–3) and 1.8 (range 1.0–2.5) were calculated for citalopram and demethylcitalopram, respectively. The mean maximum concentrations of citalopram and demethylcitalopram in milk were 154 (95% CI, 102–207) µg l(−1) and 50 (23–77) µg l(−1). Depending on the method of calculation, mean infant exposure was 3.2 or 3.7% for citalopram and 1.2 or 1.4% for demethylcitalopram. Citalopram (2.0, 2.3 and 2.3 µg l(−1)) was detected in three of the seven infants. Demethylcitalopram (2.2 and 2.2 µg l(−1)) was detected in plasma from two of the same infants. No adverse effects were seen in the infants, all were within appropriate percentile limits for weight and all had normal Denver developmental quotients. CONCLUSIONS: The mean combined dose of citalopram and demethylcitalopram (4.4–5.1% as citalopram equivalents) transmitted to infants via breast milk is below the 10% notional level of concern. Plasma concentrations of these drugs in the infants were very low or absent and there were no adverse effects. These data support the safety of the use of citalopram in breast feeding women. Nevertheless, each decision to breast feed should always be made as an individual risk:benefit analysis.